PROJECT AS AN INNOVATIVE SOLUTION FOR CHANGES IN HIGHER EDUCATION - Daniela, Linda; Kraģe, Gunta; Leskovics, Juris; Nīmante, Dita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article analyzes project as a method of innovative solution in higher education which may result in introducing gradual changes in the institutions of higher education. There is a universal opinion that universities are conservative institutions where changes are slow or they are not at all. Nowadays the emphasis of action changes and higher education institutions (hereafter in the text HEI) look for cooperation possibilities with the employers and the possible applicants; they try to get closer to the society by participating in social and economic changes that take place in the society and participate in developing the education policy and decision making. Implementation of projects in the higher education institution which involve the whole staff promotes the increase of the staff’s competence and provide innovative solutions in the study process, develop a closer link among the project partners, state, municipality and non-governmental sector.